The acute effect of diagonal reverse lunges with isometric holds on the lunge depth of badminton athletes - Carlos, Rasmine Jane V. 1999-
Late contact time during badminton lunges could lead to poor lunge execution, resulting in a disadvantaged recovery, thus an error or poor return shot. This study aimed to analyze the acute effect of the diagonal isometric reverse lunges with isometric holds on the lunge depth of badminton athletes. Thirty participants were obtained and randomly selected into two groups to perform two diagonal lunges for their pre-test and post-test trials. Prior to their post-tests, only the experimental group performed the lunge intervention (5 sets of 45-second holds with a minute of rest between sets). Lunge depth and recovery phase duration (RPD) trials were measured and analyzed in the Kinovea. Two paired and two independent t-tests with a = 0.05, were used to compare the lunge depth and RPD within each group and between groups. The effect sizes for all significant differences found were measured using Cohen's d. Results showed that the lunge intervention was feasible on the backhand lunges. This study concluded that the intervention increased the backhand’s rear leg lunge depth (experimental group) and improved their RPD. This study can help badminton sportspeople in planning training programs to enhance lunge footwork.